Preparation and Characterization of Polyaniline/Hexagonal Boron Nitride Composites - ÇAKMAKÇI, EMRAH; MADAKBAŞ, SEYFULLAH (WALTER DE GRUYTER GMBH, 2013)
Polyaniline (PANI) is one of the most studied conductive polymer with several unique properties and good conductivity. In this study it was aimed to prepare Polyaniline (PANI)/Hexagonal boron nitride (h-BN) composites. Chemical structures of the composites were characterized by FTIR analysis. Thermal properties of these novel composites were analyzed by TGA and DSC measurements. Glass transition temperatures and char yields of the composites increased with increasing h-BN percentage. FTIR, XRD and UV measurements indicated that the boron atoms in h-BN particles interact with the unpaired electrons in nitrogen atoms of PANI. Dielectric measurements revealed dipolar polarization behavior of the composites.
Keywords: PANI; h-BN; thermal analysis; complexation; XRD measurements; ELECTRICAL-PROPERTIES; FUNCTIONALIZATION; POLYMERIZATION; MORPHOLOGY; NANOTUBES